Finding minimal requirements to increase cortisol assessment reliability. (September 2021) - Laufer, S.
Abstract : The reliable assessment of cortisol data has long been a focus of research. Valuable suggestions to increase reliability have been made and majority of the scientific community nowadays follows some form of guidelines when assessing cortisol. However, the extent to which these recommendations are followed still seems to vary quite significantly. Moreover, the answer to the question, which of these recommendations are minimal requirements or "must haves" for reliable cortisol assessment can also prove to be quite challenging. As a result, methodological heterogeneity in cortisol assessment is still high. Finding a consensus with regard to the minimal requirements that enables the reliable assessment of cortisol across a broad variety of study designs may produce more reliable results and could increase between-study comparability. To this end, psychoneuroendocrinological researchers should come to an agreement, which factors are essential to ensure high data quality across the most commonly used study designs (i.e. basal and reactive cortisol assessment). In order to start this process, all participants at the 2020 conference of the ISPNE were asked to rate, which cortisol assessment recommendations and covariates they consider necessary, desirable or not necessary to reliably assess cortisol. The results of the online survey will be presented and discussed with regard to the long term goal of establishing universal minimal requirements for cortisol data collection.